PENGEMBANGAN ITIK PITALAH BERBASIS PROBIOTIK DAN PENGOLAHAN POSTHARVEST DI KECAMATAN BATIPUH KABUPATEN TANAH DATAR - Husmaini Husmaini; Firda Arlina (Jurnal Hilirisasi IPTEKS, 2021)
Pitalah ducks, a germplasm of West Sumatra, have been established through the Ministerial Decree No. 293/kpts/OT.140/6/2011. The consequence of the stipulation is seen as important in maintaining the population and purity of Pitalah ducks through the selection activities of the parents and the cultivation of Pitalah ducks in Batipuh District as an area of Pitalah ducks. One effort is to empower students to the village. The specific purpose of this activity is the development, cultivation and post-harvest processing to increase community income. This activity involved 36 Unand students. The methods used include debriefing the students, socialization activities and designing the work plans and last workshop on activity plans. The implementation of activities, namely hatching eggs produced from productive broodstock from flocks made based on the characteristics of Pitalah ducks, the from hatching is intensively cultivated so that mortality is lower and growth is faster. The growth period ducks are maintained in a semi-intensive manner utilizing local food sources namely taro, water hyacinth, ampo rice plus bran, corn and snail so that the price of feed can be cheaper. Postharvest processing is carried out by providing some innovations in processing eggs and duck meat into rendang suir, rendang eggs, various variants of salted eggs that can improve people's health and income. Based on the results of the activities that have been carried out, it can be concluded that there is a good response for the target community and local government, especially in the Batipuh sub-district, Tanah Datar Regency.